A collaboration–resilience framework for disaster management supply networks: a case study of the Philippines. Issue 4 (23rd November 2020) - Medel, Krichelle; Kousar, Rehana; Masood, Tariq
Abstract : Purpose: The increasing risk of natural disasters is challenging humanitarian actors to create resilient disaster management systems. However, the role of the private sector in disaster management operations (DMOs) is not as prominent as the role played by (inter)governmental agencies. This article aims to investigate the relationship of collaboration and resilience in disaster management supply networks (DMSNs). Design/methodology/approach: Supply network resilience criteria were defined as robustness, flexibility, velocity and visibility based on the literature review. DMSN capabilities were identified characterising each resilience criterion through the development of the Collaboration–Resilience (COLRES) Analysis Framework for DMSNs. This theoretical model was then applied to an empirical case study in the Philippines using semi-structured interviews for data gathering. Findings: A total of 46 cross-sector collaboration activities were identified across four disaster management phases and linked to the resilience criteria. A causal analysis of each collaboration activity and its outcome was conducted to identify relationships between collaboration types and resilience constructs. Based on these results, patterns were identified, and dependencies between collaboration and resilience were defined. Collective DMSN resilience (DMSNRES) enabled by existing cross-sector collaboration activities was evaluated against a future disaster scenario to identify resilience gaps. These gaps were used to recognise new cross-sector collaboration opportunities, thereby illustrating the continuous process of resilience building. Research limitations/implications: This research provides new insights on how private sector is involved within a DMOs through collaboration with the government and other NGOs. It augments existing literature on private sector involvement in DMOs where common perception is that the sector is only involved in short-term response and recovery activities. This study finds that the private sector can be operationally involved not just in post-disaster activities, but also in mitigation and preparation phases as well. This then sets a new baseline for further research on private sector involvement within DMOs. As this study provided a novel framework to analyse collaboration activities and its impact to DMSN resilience, future work could be done by applying the model to further cases such as other countries'. DMSNs, or to more specific contexts such as inter-organisational collaborations rather than big sectors. A more detailed assessment method against a future disaster will prove relevance for the model in providing practical insights on how resilience can be built in DMSNs. Practical implications: This research proposed a novel DMSN collaboration-resilience (COLRES) model (Figure 11) to analyse existing processes in preparation for specific disasters. Practitioners may be able to use this model with the goal of identifying resilience gaps to fill and continuously improve their processes. The model also provides practitioners the lens to improve processes with the perspective on collaboration to complement government and NGO efforts and expertise with those of the private sector. For the private sector perspective, this research provides new insights on how they can be more involved with the community to provide more sustainable and long-term contributions to the society. Social implications: With disasters becoming more complex and frequent by the day and as humanitarian actors focus on improving their expertise, the need for every piece of the society to contribute to disaster risk reduction is continuously intensified. This research shows that each sector of the society can take part in disaster management operations to reduce unpredictability, lives impacted and increase speed of response and recovery. Each sector of the society can be of great contribution not only during post-disaster response and recovery but also during pre-disaster mitigation and preparedness phase. As such, this research echoes the call for everyone to be involved in disaster risk reduction and mitigation as a way of life. Originality/value: This research ultimately finds that cross-sector collaboration builds resilience in DMSNs through capacity building, redundancy sourcing, information reliability and logistics responsiveness. This study shows that the private sector is able to go beyond existing short-term partnerships by participating in the 46 collaboration activities identified across four disaster management phases in order to build resilience in DMSNs.